Peripheral neuropathy in 30 duodopa patients with vitamins B supplementation. (12th June 2017) - Rispoli, V.; Simioni, V.; Capone, J. G.; Golfrè Andreasi, N.; Preda, F.; Sette, E.; Tugnoli, V.; Sensi, M.
Abstract : Objectives: Peripheral neuropathy (PN) is a significant concern and potential cause of withdrawal in patients with Parkinson's disease (PD) treated with Levodopa/Carbidopa Intestinal Gel (LCIG) infusion. Vitamin B deficiency and/or hyperhomocysteinemia levodopa‐related are considered possible causative factors. In this study, we evaluated PN incidence in LCIG‐PD patients treated since the beginning of infusion with vitamins B supplementation. Materials & Methods: In this prospective open‐label pilot study, 30 consecutive patients with PD on LCIG infusion were evaluated with clinical, neurophysiological, and biochemical assessments for a mean follow‐up of 42.4 months (range 24‐72). All evaluations were repeated every 6 months. Results: At baseline, 21 of 30 presented no signs or symptoms of PN, and 9 of 30 had pre‐existing chronic PN. In whole population, a progressive worsening in nerve conduction studies of sural sensory and peroneal motor nerves was observed during the long‐term follow‐up. 4 of 21 patients, with normal clinical, electrophysiological assessment at baseline, developed distal symmetrical axonal polyneuropathy that remained asymptomatic during the long‐term follow‐up. Patients with pre‐existing PN (9 of 30) showed a mild worsening of electrophysiological features during the period of observation. In none PN was cause of discontinuation of LCIG therapy. No incident cases of acute‐subacute PN were documented. No correlation was found with age, sex, Levodopa dosage, duration of levodopa exposure, and homocysteine plasma levels. Conclusion: In this consecutive series of 30 patients with PD on LCIG infusion, with early and continuous vitamins B integration, we observed a low rate (19%) of new onset peripheral polyneuropathy that remained stable after long‐term follow‐up. Larger studies, controlled, with blinded evaluation, are needed to confirm these findings.